2016
DOI: 10.1073/pnas.1605841113
|View full text |Cite
|
Sign up to set email alerts
|

Theranostic near-infrared fluorescent nanoplatform for imaging and systemic siRNA delivery to metastatic anaplastic thyroid cancer

Abstract: Anaplastic thyroid cancer (ATC), one of the most aggressive solid tumors, is characterized by rapid tumor growth and severe metastasis to other organs. Owing to the lack of effective treatment options, ATC has a mortality rate of ∼100% and median survival of less than 5 months. RNAi nanotechnology represents a promising strategy for cancer therapy through nanoparticle (NP) -mediated delivery of RNAi agents (e.g., siRNA) to solid tumors for specific silencing of target genes driving growth and/or metastasis. Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 28 publications
1
58
0
Order By: Relevance
“…It has also been increasingly recognized that the EPR effect, the dominant mechanism that mediates the tumor accumulation of nanomaterials, varies among patients and tumor types and even within the same patient/tumor type over time, [18] which highlighted the need to incorporate the imaging function into nanomedicines to identify cancer patients with stronger EPR effects and higher tumor accumulation of nanomedicines for more efficient cancer treatment. [19] …”
Section: Resultsmentioning
confidence: 99%
“…It has also been increasingly recognized that the EPR effect, the dominant mechanism that mediates the tumor accumulation of nanomaterials, varies among patients and tumor types and even within the same patient/tumor type over time, [18] which highlighted the need to incorporate the imaging function into nanomedicines to identify cancer patients with stronger EPR effects and higher tumor accumulation of nanomedicines for more efficient cancer treatment. [19] …”
Section: Resultsmentioning
confidence: 99%
“…ERK1/2) [8]. Using RNA interference (siRNA) to knock down BRAF in human ATC cell lines, preclinical studies showed the importance of BRAF for intracellular MAPK signaling and proliferation, as tumor growth was significantly inhibited [9,10]. These findings suggested that BRAF could be an effective target for thyroid cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Vemurafenib/PLX4032 is a selective small molecule inhibitor of B-RafV600E, showing a preferential inhibition of cell proliferation, migration, and invasion of BRAFV600E human ATC cell lines [10][11][12][13]. Furthermore, vemurafenib decreased tumor growth and aggressiveness in an animal model using human ATC cell lines [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the integration of therapy and diagnostics termed “theranostics” has led to the development of new and improved gene therapeutics for the diagnosis and treatment of cancers (Sumer & Gao, ). Specifically, siRNA bioconjugates containing reporter probes such as fluorophores, near‐infrared (near IR) dyes and photosensitizers as well as those containing contrast agents and radiolabels (Figure b) have been extensively applied as theranostic agents in oncology (Liu et al., ; Zhao, Mi, & Feng, ). In spite of the many fruitful examples of siRNA bioconjugation and their applications in cancer gene therapy, a major limitation is the restriction of a single functional moiety on either the 3′ or 5′ ends of the oligonucleotide.…”
Section: Introductionmentioning
confidence: 99%